GIS, remote sensing and spatial analysis for vector-borne diseases - Kitron, Uriel; Vazquez-Prokopec, Gonzalo (Henry Stewart Talks, 2010)
Spatial aspects in surveillance and research, Tools for spatial analysis, Spatial statistics, Landscape ecology, Scale and resolution, Risk maps, Three examples: West Nile Virus in Chicago, Chagas disease in Argentina and Dengue in Australia, Opportunities and limitations